Design and Implementation of IOT and RFID Payment Solutions for a Solar-Powered Wireless EV Charging Station (International Journal of Scientific Research in Science and Technology, 2025)
This project presents a solar-powered, wireless Electric Vehicle (EV) charging station that integrates IoT connectivity and RFID-based payment solutions to deliver a secure, sustainable, and user-friendly charging experience. The system harnesses solar energy through a photovoltaic panel that charges a 12V battery via a dedicated charging circuit. An Arduino-based control system serves as the central hub, managing energy monitoring, EV charging operations, and communication functionalities. A voltage sensor continuously monitors the solar panel output, enabling real-time energy management and ensuring optimal performance. To maintain uninterrupted operation, an auxiliary power supply automatically engages when solar energy is insufficient. The implementation of RFID technology facilitates secure, contactless payment, where user authentication triggers a relay module that activates a wireless transmitter. This transmitter establishes a secure connection with the EV’s receiver, thereby initiating the charging process. Experimental evaluations confirm the system’s effectiveness in integrating renewable energy, ensuring operational flexibility, and enhancing security in EV charging applications.